(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Oneof the most prominent developments in the banking industry has been the strongworldwide consolidation observed during the past decades. This is rejected by asharp fall in the number of banks, increased concentration, and the increasedsize of the largest banks both in absolute terms and relative to the smallerbanks.